Labor Force Dynamics of Older Men - Blau, David M. (Econometrica, 1994)
"This paper describes and analyzes movements of older men among labor force states [in the United States] using quarterly observations derived from the Retirement History Survey (RHS)." The results indicate "substantial undercounts in the biannual data, indicating that the prevalence of labor force movements at older ages has been underestimated previously.... The results show that labor force dynamics at older ages are important, including duration and spell occurrence dependence, and work experience effects. These effects are robust to nonparametric controls for unobserved heterogeneity. The estimates indicate that social security benefits have strong effects on the timing of labor force transitions at older ages, but that changes in social security benefit levels over time have not contributed much to the trend toward earlier labor force exit."